Size and modality effects in Braille learning: Implications for the blind child from pre‐reading sighted children. (17th June 2018) - Barlow‐Brown, Fiona; Barker, Christopher; Harris, Margaret
Abstract : Background: Beginning readers are typically introduced to enlarged print, and the size of this print decreases as readers become more fluent. In comparison, beginning blind readers are expected to learn standard‐sized Braille from the outset because past research suggests letter knowledge cannot be transferred across different sizes of Braille. Aims: The study aims to investigate whether learning Braille using an oversized pegboard leads to faster, transferable, letter learning and whether performance is mediated by either tactile or visual learning. Sample: Sixty‐eight children participated in the study. All children were sighted pre‐readers with no previous knowledge of Braille. The children came from two nursery schools with an average age of 47.8 months. Methods: Children were taught specific Braille letters using either an enlarged pegboard or standard Braille. Two other groups of children were taught using visually presented Braille characters in either an enlarged or standard size and a further control group mirrored the experience of blind children in receiving non‐specific tactile training prior to being introduced to Braille. In all tactile conditions it was ensured that the children did not visually experience any Braille for the duration of the study. Results: Results demonstrated that initially training children with large Braille tactually led to the best subsequent learning of standard Braille. Despite the fact that both initial visual and large tactual learning were significantly faster than learning standard Braille, when transferring letter knowledge to standard tactile Braille, previous tactile experience with the large pegboard offered the most efficient route. Conclusions: Braille letter knowledge can be transferred across size and modality particularly effectively with large tactile Braille. This has significant implications for the education of blind children.